ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN KELAS IBU HAMIL DI PUSKESMAS SIMPANG KANAN KOTA SUBULUSSALAM PROVINSI ACEH - Ivasri Marsaulina (Universitas Prima Indonesia, 2024)
According to WHO, more than 350,000 women worldwide die each year from complications of pregnancy and childbirth. IDHS data on the number of cases of maternal death during childbirth decreased from 4,999 cases in 2015 to 4,912 cases in 2016. Meanwhile, until the first semester of 2017 there were 1,712 cases of maternal death during childbirth. Efforts to accelerate the decline in MMR, the government has set many strategies and policies in the form of health improvement programs by conducting classes for pregnant women. The purpose of this research is to analyze factors that affect the implementation of classes for pregnant women in the Simpang Kiri Health Center Work Area, Subulussalam City, Aceh Province in 2020